2019
DOI: 10.1088/1757-899x/577/1/012137
|View full text |Cite
|
Sign up to set email alerts
|

Structural and photocatalytic degradation studies of rice straw based MgO nanocomposite

Abstract: The present study is focused on the comparison of structural and photocatalytic degradation activities of nanocomposite of MgO formed with rice straw, a biopolymer. For comparison, counter parts were also synthesized. Nanoparticles of magnesium oxide were synthesized through controlled co-precipitation method in presence of citric acid. Structural characterizations of all the synthesized samples were carried out using XRD. Comparison of XRD of metal oxide with JCPDS confirmed that the formed metal oxide was Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…[18] Several investigations have shown that rice straw-based metal oxide nanocomposite is good for photodegradation of organic dye. [19][20][21] The present study was undertaken to prepare different catalytic composite systems based on rice straw ash (RSA) modified by nano-TiO 2 (anatase) and copper phthalocyanine (CuPc) namely, RSA-TiO 2 , RSA-CuPc, and RSA-TiO 2 -CuPc. The as-prepared composite systems were characterized by several physicochemical techniques and their catalytic performances in photodegradation of methylene blue dye were evaluated under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Several investigations have shown that rice straw-based metal oxide nanocomposite is good for photodegradation of organic dye. [19][20][21] The present study was undertaken to prepare different catalytic composite systems based on rice straw ash (RSA) modified by nano-TiO 2 (anatase) and copper phthalocyanine (CuPc) namely, RSA-TiO 2 , RSA-CuPc, and RSA-TiO 2 -CuPc. The as-prepared composite systems were characterized by several physicochemical techniques and their catalytic performances in photodegradation of methylene blue dye were evaluated under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%